Hydrological behavior of a mesoscale montane catchment in central-eastern Mexico - Guzmán Huerta, Alitzel; Muñoz Villers, Lyssette Elena (BOSQUE, 2021)
Cloud forests are ecosystems with high hydrological value, however, land use change and the modification of climate patterns are increasingly threatening their existence. This study examined the hydrological behavior of the Los Gavilanes river catchment (~ 35 km2) that supplies 90 % of water to the city of Coatepec (Veracruz, México) and surrounding areas. Rainfall was registered using automatic rain gauges and streamflow was measured using water level readings from pressure transducers in combination with stream gauging methods. Annual rainfall (2015-2016) was 2,692 mm distributed in 177 events with mean rainfall amounts and average intensities of 22.6 mm and 6.5 mm hr-1 during the wet season, respectively, and 11.4 mm and 1.6 mm hr-1 during the dry season. Annual streamflow was 1,394 mm, of which 90 % was baseflow with no seasonal differences observed. In general, the catchment’s hydrological response shows a clear signal of its high rainfall infiltration and water storage capacity, characteristics preserved by the forest cover, allowing to sustain streamflow and the provision of water sources for the region throughout the year. Finally, maximum rain event intensities and amounts were the key variables explaining quickflow and baseflow generation and total discharge in the study catchment.